Expectations About Specific Training in Physical Activities in Natural Environment in The Bachelor’s Degree in Primary School Teaching (GYMNASIUM, 2019)
This work shows the opinion on the specific training in physical activities in natural environment of the Teaching in Primary Education Students of the Faculty of Education (University of Zaragoza). 208 students were surveyed voluntarily during the 2019/20 academic year. They were students of the two subjects whose contents were object of the survey. The questionnaire used contained a 5-point likert scale. The students answered about the influence of these activities on the acquisition of personal, prosocial and training competencies. The highest scores in transversal competencies corresponded to student involvement (4.41 ±.744), teamwork (4.38 ±.758) and research on the practice itself (4.22 ±.761).  Furthermore, respect (4.59 ±.638) and cooperation (4.56 ±.603) were the most valued personal competencies. These issues should serve to guide teachers to redirect a better methodology in their subjects. This work can be extrapolated to any university institution with specific teaching on physical activities in natural environment.